Preparation of TiO2/Fe3O4 composite by sol-gel method and its photocatalytic activity for removal of Rhodamine B from water. (3rd July 2020) - Tang, Peisong; Ding, Yangbin; Chen, Haifeng; Wang, Yongya
Abstract: The TiO2 /Fe3 O4 composite is a new kind of photocatalytic materials with magnetism. Using FeCl2, FeCl3, and titanyl sulfate as the main raw material, TiO2 /Fe3 O4 was synthesized by sol-gel process and 450 °C calcination for 2 h under a condition of hydrogen nitrogen mixture gas. The samples were characterized by powder X-ray diffraction (XRD), fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The photocatalytic activity, reclaim and cyclic utilization of the TiO2 /Fe3 O4 composite were studied by using Rhodamine B as simulated wastewater. The results show that TiO2 /Fe3 O4 composite has good magnetic properties and excellent photocatalytic activity for removal of Rhodamine B from water, and it can come true well reclaim and recycling by using the electromagnet. The recovery efficiency of TiO2 /Fe3 O4 composite can reach above 90% at the first reclaiming. TiO2 /Fe3 O4 composite can be reused tree times without a significant photoactivity loss. It shows that TiO2 /Fe3 O4 composite is a kind of environmental photocatalyst with a wide application prospects.